ANALISIS KONSUMSI PANGAN TINGKAT MASYARAKAT MENDUKUNG PENCAPAIAN DIVERSIFIKASI PANGAN - Ariani, Mewa (PERSATUAN AHLI GIZI INDONESIA, 2010)
THE ANALYSIS OF FOOD CONSUMPTION AT COMMUNITY LEVEL TO ACHIEVE FOOD DIVERSIFICATIONAs a country with large population, having food-self-sufficiency-based-food security is very important. One of the strategies to be secured in food-self-sufficiency-based-food is through achieving food consumption diversification. This paper was aimed to analyze recent food consumption pattern in Indonesia with respect to food consumption diversification. Source of the data was National Household Socio-economic Survey (SUSENAS) year 2005-2009 obtained from the Food Security Council, Ministry of Agriculture. The data were analyzed using quantitative descriptive method and presented i n tables. Results of the analyses showed that: 1) Community’s welfare in Indonesia is improving, showed by reducing proportion of food expenditure; 2) Protein consumption among Indonesian people exceeds Recommended Dietary Allowance (RDA) for protein, while energy consumption is still below RDA for energy; and 3) The diversity of food consumption pattern among Indonesian people is improving, showed by increasing Dietary Diversity Score (Pola Pangan Harapan/PPH). However, to reach PPH-based food pattern, rice consumption should be limited, while consumption of tubers, animal food and fruitsvegetables still has to be increased significantly. Government created various instruments to achieve food diversification, such as Regulation of President No. 22, 2009 about Local Resources-based-Accelerating Food Consumption Diversification Policy, which further regulated by Ministry of Agriculture based on Regulation of Minister of Agriculture No. 43, 2009 about the action. Learning from past experience, simultaneous commitment and consistency from all stakeholders including legislative institution and media (newspaper, TV, radio, etc.) is important to implement. By having similar perception, right action and consistency in implementation, food diversification is no longer being a dream.Keywords: food diversification, food consumption, community